Artificial intelligence literacy, English learning materials, and career readiness in digital workplace environment: An explanatory study - Yusi Rahmawati (Journal of Educational Management and Instruction (JEMIN), 2026)
The rapid advancement of generative artificial intelligence (AI) has transformed educational and professional environments, yet the integration of AI literacy within English for Specific Purposes (ESP) learning materials remains limited, particularly in vocational education contexts. This study investigates the influence of AI literacy, the relevance of ESP materials to AI development, and students’ perceptions of AI-based learning on career readiness in digitally transformed workplaces. Employing an explanatory quantitative design, the study involved 186 cadets from a maritime vocational higher education institution in Semarang, Indonesia. Data were collected using a closed-ended Likert-scale questionnaire and analyzed through descriptive statistics, classical assumption testing, and path analysis. The findings reveal that AI literacy significantly influences career readiness both directly and indirectly through students’ perceptions of AI-based learning. In addition, the relevance of ESP instructional materials to emerging AI trends significantly contributes to students’ preparedness for digital professional environments. The mediating role of perception indicates that positive attitudes toward AI-supported learning strengthen the relationship between AI literacy and career readiness. These findings highlight the importance of redesigning ESP curricula and instructional materials to integrate AI literacy, authentic digital communication practices, and technology-oriented learning experiences that better align with contemporary workforce demands.